Modelación y comovimientos de la tasa de cambio colombiana, 2011-2017; Modeling and comovements of the Colombian exchange rate, 2011-2017 - Giuliana Maya Sierra; Nini Johana Marin Rodríguez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– The exchange rate is influenced by multiple national and international macroeconomic factors, which generates high levels of uncertainty. The objective of this research is the construction of ARIMA-GARCH and ARIMAX-GARCH models as a tool for the forecast of the exchange rate in Colombia from the daily returns of the closing prices USD/COP and its analysis of dynamic correlation with some of the most explicative variables. The results suggest that the incorporation of significant exogenous variables within the ARIMAX-GARCH model with persistent correlation according to the DCC (Dinamic Conditional Correlation) model to the USD/COP pair generates out-of-sample forecasts with better performance than the ARIMA-GARCH univariate models.
Keywords: E6; C51; F31; C30; 330; Macroeconomic fundamentals; forecast models; exchange rate; correlation